2014
DOI: 10.1037/a0036552
|View full text |Cite
|
Sign up to set email alerts
|

Attentional inertia and delayed orienting of spatial attention in task-switching.

Abstract: Spatial attention in task-switching Author note:The research presented in this paper was carried out by Cai Longman for his PhD under the supervision of Aureliu Lavric and Stephen Monsell. We are grateful to CristianMunteanu for the help in programming some of the more involved analyses.Longman, Lavric & Monsell 3 Spatial attention in task-switching AbstractAmong the potential, but neglected, sources of task-switch costs is the need to reallocate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
118
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(146 citation statements)
references
References 76 publications
19
118
9
Order By: Relevance
“…Lien et al (2010) found that an irrelevant stimulus presented shortly before stimulus onset captured attention only when its color was task-relevant, and that this contingent capture effect was uninfluenced by task switch/repeat, suggesting that task-set preparation during the interval was completely effective in reconfiguring the feature set and thus suppressing capture by the irrelevant color. Experiments in our lab (Longman, Lavric & Monsell, 2013;Longman, Lavric, Munteanu, & Monsell, 2014) have led to a different conclusion for spatial attention. Using tasks consistently associated with different spatial locations, and eye-tracking to index spatial attention, we found that task-switching induces both substantial delays in orienting appropriately, and a tendency to fixate the target location appropriate to the previous task, even with a generous interval for preparation.…”
Section: Other Evidence For Attentional Inertiamentioning
confidence: 99%
“…Lien et al (2010) found that an irrelevant stimulus presented shortly before stimulus onset captured attention only when its color was task-relevant, and that this contingent capture effect was uninfluenced by task switch/repeat, suggesting that task-set preparation during the interval was completely effective in reconfiguring the feature set and thus suppressing capture by the irrelevant color. Experiments in our lab (Longman, Lavric & Monsell, 2013;Longman, Lavric, Munteanu, & Monsell, 2014) have led to a different conclusion for spatial attention. Using tasks consistently associated with different spatial locations, and eye-tracking to index spatial attention, we found that task-switching induces both substantial delays in orienting appropriately, and a tendency to fixate the target location appropriate to the previous task, even with a generous interval for preparation.…”
Section: Other Evidence For Attentional Inertiamentioning
confidence: 99%
“…Thus, cue availability during the CTI, cue status after target onset, or the combination of both attributes might have been responsible for the findings of Verbruggen et al (2007). However, their experiments do not allow one to distinguish between the potential effects of these attributes, and other studies have yielded inconclusive results.In some previous studies, residual switch costs have been observed when the cue was partially available during the CTI and remained absent after target onset (Lenartowicz, Yeung, & Cohen, 2011;Longman et al, 2014;Mayr, 2001;Steinhauser, Maier, & Hübner, 2007;Yamaguchi & Proctor, 2011), but they lacked typical cuing conditions for comparison. In other studies, residual switch costs have been observed when cue status after target onset was manipulated, with the cue always being available for the full CTI (Gotler & Meiran, 2001;Proctor, Koch, Vu, & Yamaguchi, 2008).…”
mentioning
confidence: 99%
“…First, it is common to present the cue before the target, with the time from cue onset to target onset referred to as the cue-target interval (CTI). Studies in which the CTI has been manipulated have revealed that response times (RTs) become shorter and switch costs decrease with longer CTIs (e.g., Monsell & Mizon, 2006;Schneider & Logan, 2011), although residual switch costs have been observed after CTIs of 1,000 ms or longer (e.g., Longman, Lavric, Munteanu, & Monsell, 2014;Meiran, 1996;Meiran et al, 2000). Second, the cue (often a visual stimulus) is typically available for the full CTI and remains present after target onset.…”
mentioning
confidence: 99%
“…In the current Experiment 1, we modified Longman et al's (2014) task-switching conditions by introducing cues and instructions designed to prioritise shifting of the attentional component, and found that this appeared to decouple its reconfiguration from the rest of task set. In Experiment 2, we used (arbitrary) symbolic cues with the same instructions and training, and found that the pattern of data reverted to that suggesting largely integrated reconfiguration of the whole task-set.…”
mentioning
confidence: 99%
“…We took a situation where we already have evidence, from on-line measurement of direction of gaze, for strong coupling between reconfiguration of spatial attention and other components of task-set (Longman, Lavric, & Monsell, 2013;Longman, Lavric, Munteanu, & Monsell, 2014). …”
mentioning
confidence: 99%